2017
DOI: 10.1177/1756829317745318
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the head-up pitching moment of small quad-rotor unmanned aerial vehicles in uniform flow

Abstract: Multi-rotor unmanned aerial vehicles are unstable in headwind because of nose-up pitching moment generation and thrust degradation. Reducing the pitching moment generation could enhance the tolerance of the unmanned aerial vehicles to wind and improve cruise flight speed. In this study, a canted rotor configuration was proposed to reduce the moment in uniform flow and examined. The objective of the study is to evaluate the effect of moment reduction by canted rotors. First, flow interactions between rotors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Additionally, for preflight planning, Barnas et al [85] suggested fixed-wing systems' stability is optimized by flying directed to the crosswind rather than into headwind or tailwind. For multirotors flying into headwinds, slanting the rotors by 20 degrees can reduce upwards pitching by 26% [137]. Heavy, bulky equipment should be avoided, such as the Sirius Pro from MAVinci, the UX5 from Trimble, of the Q-200 from Quest UAS for applications in high elevation [34].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Additionally, for preflight planning, Barnas et al [85] suggested fixed-wing systems' stability is optimized by flying directed to the crosswind rather than into headwind or tailwind. For multirotors flying into headwinds, slanting the rotors by 20 degrees can reduce upwards pitching by 26% [137]. Heavy, bulky equipment should be avoided, such as the Sirius Pro from MAVinci, the UX5 from Trimble, of the Q-200 from Quest UAS for applications in high elevation [34].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The trimmed variables are the pitch angle and the left and right rotor speeds denoted by θ, Ω and Ωr , respectively. Setting the position and pitch rates and accelerations to zero in ( 13)- (22) gives…”
Section: Vehicle Trimmentioning
confidence: 99%
“…and the aerodynamic forces, T i , H i , are dependent upon the state, x, control, u and wind disturbance V W . The dynamic equations, ( 13)- (22), are linearized at a set of trim points using the second order finite difference method ( [37], p. 200). This gives the small perturbation model…”
Section: Model With Rotor Aerodynamicsmentioning
confidence: 99%
See 2 more Smart Citations